Uji Kualitas Buah Nanas MD2 Tanpa Mahkota Buah - Sari, Reny Mita; Sesanti, Rizka Novi; Ali, Fahri (J-Plantasimbiosa, 2025)
Pineapple is one of high value fruit commodities in Indonesia. Some sellers and consumers are prefer decrowned pineapples to simplify postharvest handling. This study aimed to investigate the effect of decrowned pineapple to fruit quality and eating quality of MD2 pineapples after 7 days of storage. The research was conducted using a completely randomized design (CRD) with three treatments: pineapples at day 0 (H0), pineapples with the crown after 7 days storage (CH7), and decrowned pineapples after 7 days storage (DH7). The results showed that decrowned pineapple significantly affected weight loss, fruit maturity, aroma, and taste of MD2 pineapples. Decrowned fruit accelerated the ripening process, as indicated by a higher maturity index compared to pineapples with the crown, and was also associated with the emergence of an alcoholic aroma and flavor in the fruit flesh. Keywords : pineapple, crown removal, eating quality